Occupational performance coaching for stroke survivors delivered via telerehabilitation using a single-case experimental design. (August 2021) - Kessler, Dorothy; Anderson, Nicole D; Dawson, Deirdre R
Introduction: Sustaining a stroke has a devastating, long-term impact on participation in everyday life. Despite the recognition of participation as a key outcome of stroke rehabilitation, there are few effective interventions that address participation. Occupational performance coaching is a promising intervention designed to improve participation among stroke survivors. Delivery of occupational performance coaching using telerehabilitation could improve access. This study examined the feasibility, acceptability and potential efficacy of telerehabilitation occupational performance coaching. Method: A single-case experimental design was used. Six community-dwelling stroke survivors received 10 sessions of telerehabilitation occupational performance coaching over 16 weeks. We examined the feasibility and acceptability of telerehabilitation occupational performance coaching, improvement in performance and satisfaction with identified goals. Results: Telerehabilitation occupational performance coaching was feasible and acceptable to deliver; participants who started the intervention completed it and reported high satisfaction and a strong therapeutic relationship. All participants experienced technological issues that required resolution. Goal-performance and/or satisfaction improved for five of six participants. Sixty-four percent of goals showed trends for improvement and 43% showed significant improvements. Conclusions: Findings support the feasibility and acceptability of telerehabilitation occupational performance coaching, along with its efficacy for improving performance and satisfaction with performance of goals. Further research is needed to prove the effectiveness of telerehabilitation occupational performance coaching and to determine who may benefit most.